Impact of mental health, job insecurity, and COVID-19 symptoms on protective behavior changes among White, Black, and other minorities in the US - Sun, Yingying; Wang, Ping; Tang, Jun (Frontiers in Psychology, 2022)
Job insecurity such as loss of jobs or reduced wages has become a serious social problem since COVID-19 started. Combined with psychological distress and experience of COVID-19 symptoms, the changes of people’s protective behaviors vary across states in the US. This research investigated racial differences in the COVID-19 related factors among White, Black, and other minorities in the US, and examined how mental health mediated the impact of job insecurity on protective behaviors, and how the COVID-19 symptoms moderated the mediation effect of mental health. The 731 valid responses in a cross-sectional survey from May 23 to 27, 2020, in the US were analyzed with independent sample t-tests, Pearson’s chi-square tests, and path analysis. The findings of this study showed that there were significant differences in job insecurity and NPI practice among White, Black, and other minorities. Job insecurity was significantly negatively associated with NPI practice and was significantly positively associated with mental health. Mental health significantly partially mediated the impact of job insecurity on NPI practice, in that job insecurity is a better predictor of NPI practice for individuals with worse mental health than for individuals with better mental health. Experience of COVID-19 symptoms moderates job insecurity and affects NPI practice through mental health, in that mental health is a better predictor of NPI practice for individuals with a higher experience with COVID-19 symptoms than for individuals with a lower experience with COVID-19 symptoms. The findings in this study shed lights on psychological and behavioral studies of people’s behavior changes during a pandemic. The study indicates the importance of treating mental health to promote protective behaviors during a pandemic, as well as advocating for employees by identifying the needs for those whose jobs were negatively impacted the most.